SENI PERTUNJUKAN TRADISIONAL DI PERSIMPANGAN ZAMAN: STUDI KASUS KESENIAN MENAK KONCER SUMOWONO SEMARANG - Andri R.M., Laura (Faculty of Humanities, Diponegoro University, 2016)
In Indonesia, each province has its own traditional culture. Traditional arts are used to express the beauty of the human soul. In traditional artwork implicit message of the society of knowledge, ideas, beliefs and values norms. In addition to the function of rituals, traditional performing arts is also being used to honor and commemorate the influential figures in the local community, heroism, patriotism and nationalism. One example of a traditional art that has the functionality is Menak Koncer. Menak Koncer is a community-owned art Sumowono, Kabupaten Semarang, Jawa Tengah raised to preserve the culture and values in society. Through a qualitative descriptive approach with observation techniques and literature, it was found that at the next stage of development, especially in the modern society, arts performances Menak Koncer shift function just as mere entertainment. Menak Koncer existence as art and traditional culture in Indonesia progressively eroded by the expansion of global art and culture. Therefore, efforts must be made to preserve the arts and culture in the midst of changing times and foreign cultural influences have been increasing in Indonesia.